Cognitive decline in prostate cancer patients undergoing ADT: a potential role for exercise training. Issue 4 (April 2017) - Mundell, Niamh L; Daly, Robin M; Macpherson, Helen; Fraser, Steve F
Abstract : Androgen deprivation therapy (ADT) is an effective and widely prescribed treatment for prostate cancer (PCa), but it is associated with multiple treatment-induced adverse effects that impact on various musculoskeletal and cardiometabolic health outcomes. Emerging research has shown that ADT is also associated with cognitive impairment, which has been linked to a loss of independence, increased falls and fracture risk and greater use of medical services. The aim of this review is to outline the evidence related to the effect of ADT use on cognitive function, and propose a role for exercise training as part of usual care to prevent and/or manage cognitive impairments for PCa survivors on ADT. The following results have been obtained from this study. ADT has been shown to adversely affect specific cognitive domains, particularly verbal memory, visuomotor function, attention and executive function. However, current clinical guidelines do not recommend routine assessment of cognitive function in these men. No studies have examined whether exercise training can preserve or improve cognitive function in these men, but in healthy adults', multimodal exercise training incorporating aerobic training, progressive resistance training (PRT) and challenging motor control exercises have the potential to attenuate cognitive decline. In conclusion, as treatment with ADT for men with PCa has been associated with a decline in cognition, it is recommended that cognitive function be routinely monitored in these men and that regular exercise training be prescribed to preserve (or improve) cognitive function. Assessment of cognition and individualised exercise training should be considered in the usual treatment plan of PCa patients receiving ADT.